Morphological Analysis of The Novel Fatamorgana by Prilly Latuconsina: Morfologi, Afiksasi, Reduplikasi - Fadiah Khoriunnisa Salkeri; Aninditya Sri Nugraheni (Universitas Muria Kudus, 2026)
The problem in this study is how to understand the shape of phonemes in morphological studies. The purpose of this research is to describe the use of morphological vocabulary in the novel Mirage by Prilly Latuconsina. This study uses a qualitative method research approach, namely by analyzing the research object objectively, morphological analysis in the novel Mirage chapter 1 by Prilly Latuconsina. The result was the morphology of a literary work entitled